2018
DOI: 10.1371/journal.pbio.2006893
|View full text |Cite
|
Sign up to set email alerts
|

Experimental bacterial adaptation to the zebrafish gut reveals a primary role for immigration

Abstract: All animals live in intimate association with microorganisms that profoundly influence their health and development, yet the traits that allow microorganisms to establish and maintain host associations are not well understood. To date, most investigations aimed at identifying traits required for host association have focused on intrahost niches. Consequently, little is known about the relative contribution of extrahost factors such as environmental growth and survival and immigration into hosts from the extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 74 publications
7
94
0
Order By: Relevance
“…Another option is that after bacterial cells migrate into the digestive tract, motility could help bacteria resist expulsion induced by intestinal contractions [39]. Ultimately, our results add to a growing body of evidence implicating motility as an important trait for host colonization [14, 17, 29, 59], and the phenotypic parallelism we observed suggests that traits associated with dispersal can play a critical role in the establishment of host-microbe symbioses [60].…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Another option is that after bacterial cells migrate into the digestive tract, motility could help bacteria resist expulsion induced by intestinal contractions [39]. Ultimately, our results add to a growing body of evidence implicating motility as an important trait for host colonization [14, 17, 29, 59], and the phenotypic parallelism we observed suggests that traits associated with dispersal can play a critical role in the establishment of host-microbe symbioses [60].…”
Section: Discussionsupporting
confidence: 53%
“…Since Robinson and colleagues previously demonstrated that serially passaged Aeromonas populations, which were more motile than an unpassaged ancestor, were able to better colonize GF larval zebrafish [29], we hypothesized that MR-1 could similarly improve host colonization in our study via enhanced motility. A common assumption in microbiology is that there is a trade-off between adherence and motility [4245], wherein cells that tend to be more adherent also tend to be less motile and vice versa.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations